Effect of 1 Year of Qigong Exercise on Cognitive Function Among Older Chinese Adults at Risk of Cognitive Decline: A Cluster Randomized Controlled Trial - Jin, Jing; Wu, Yin; Li, Shaohua; Jin, Suhui; Wang, Lin; Zhang, Jian; Zhou, Chenglin; Gao, Yong; Wang, Zhen (Frontiers in Psychology, 2020)
Background: The rapidly aging Chinese population is showing an increase in age-related illnesses, including mild cognitive impairment and Alzheimer disease. The best types of physical activity for the improvement of cognition remain unknown. This study aimed to compare the effectiveness of a tailored qigong exercise with that of stretching exercise in the maintenance of cognitive abilities in Chinese elders at risk of cognitive decline. Methods: Seventy-four community-dwelling adults aged ≥60 years were screened for eligibility. Using a randomized control group design, participants with scores ≥19 on the Chinese version of the Montreal Cognitive Assessment-Basic (MoCA) were allocated to a 1-year qigong intervention (n = 33) and a stretching control exercise group (n = 33). The primary outcome was the MoCA score, as a measure of global cognitive function, and secondary outcomes were globe cognition and five domain scores on the Chinese version of the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). The MoCA and RBANS were administered at baseline and 1 year after intervention to assess the effect of the exercises on cognitive decline. Results: Twenty-five of 33 (75.8%) participants in the qigong group and 26 of 33 (78.8%) participants in the control group completed the 1-year exercise programs. A bivariate test revealed strong correlation between MoCA and RBANS total scores after the intervention (r = 0.517, p < 0.01). Generalized estimating equations revealed a lower risk of progression of cognitive decline at 1 year in the qigong group than in the control group (odds ratio, 0.314; 95% confidence interval, 0.103–0.961; p = 0.04). Two-way repeated-measures ANOVA followed by post hoc t tests with Bonferroni corrections indicated that MoCA and RBANS scores were significantly higher in the qigong group than in the control group (MoCA and RBANS global cognition, memory, visuospatial/constructional ability, and language, all p < 0.01), with the exception of RBANS attention score (p > 0.05). Conclusions: One year of qigong practice was significantly superior to stretching exercise not only for the prevention of cognitive decline progression, but also for the improvement of several cognitive functions, among older Chinese adults at risk of cognitive decline.